Elastoplastic folding behavior of membrane ribbon based on plane strain beam theory. (15th June 2018) - Xia, Z.M.; Wang, C.G.; Tan, H.F.
Highlights: An elastoplastic folding model is proposed based on plane strain beam theory. The results predicted by the theoretical model are verified by the experiments and simulations. A plastic unloading phenomenon during the folding is found by the numerical simulation. The obtained critical folding force is meaningful for the crease-free design during the folding. Abstract: This paper studies the folding mechanical behaviors of Z-fold membrane ribbon. An elastoplastic folding model is proposed based on the plane strain beam theory, in which a power-law hardening material relation is considered. The folding mechanical characteristics, such as folding force, folding space and shape, are obtained by using the proposed model. The folding experiments and simulations are conducted and the results from experiments and simulations are compared to verify the proposed model. The results in this paper are helpful for the deep understanding of the elastoplastic folding behavior, and the obtained critical folding force or space can be used to guide the crease-free design during the folding. Graphical abstract: Image, graphical abstract